The Pearson complete course for CISM certification. - Greene, Sari Stern, 1957- (LiveLessons (Boston, Massachusetts), 2022)
18+ hours of video training to prepare you for the CISM certification exam Overview: The Pearson Complete Course for CISM Certification offers 18 hours of targeted training to help you get the skills you need to successfully study for the CISM exam. Taught by expert author and trainer Sari Greene, the course covers the four main domains of the CISM exam: Information Security Governance, Information Security Risk Management, Information Security Program Development and Management and Incident Management. The course is also a great resource for anyone who wants to enhance their cybersecurity skills to grow their career. The Pearson Complete Course for CISM Certification will enable you to learn the skills to design, deploy and manage security policies. The course starts with a basic introduction of the exam modules and topic domains before diving deeper into the main modules which incorporate real-world scenarios and practical applications. Each lesson concludes with a review and a quiz, giving you the opportunity to test what you have learned in the lesson. The course also provides tips and valuable information on how to answer questions and ace the CISM certification exam. This accessible self-paced video training provides learners with more than 18 hours of in-depth exam topic assessment from one of the leading cybersecurity experts to review each exam objective, so you can use it as a complete study tool for taking the CISM certification exam. Topics include: Module 1: Information Security Governance Module 2: Information Security Risk Management Module 3: Information Security Program Development & Management Module 4: Incident Management Module 5: Attaining Your Certification Skill Level: Intermediate to Advanced Learn How To: Govern information and cybersecurity fundamentals Strategize information strategy Manage information security risk Manage penetration testing Develop and manage InfoSec program ecosystem Design and implement wireless connectivity, firewalls, and encryption Manage malware and social engineering Who Should Take This Course: Primary audience is anyone preparing for the ISACA CISM certification examination. Secondary audience is anyone would be like to enhance their cybersecurity skills. About Pearson Video Training: Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Sams, and Que Topics include: IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.